integrated ultrasound (2d, doppler color, 3d) in the prediction of ovarian cancer - Huamán Guerrero, M. (2015)
Objective: To determine the predictive value of integrated US study (2D, Doppler color, 3D) in the differentiation of benign and malignant ovarian tumours. Design: Longitudinal comparative study. Setting: Instituto Latinoamericano de Salud Reproductiva (ILSAR). Participants: Women with ovarían tumours referred from Hospital Nacional Dos de Mayo. Interventions: One hundred and one women with ovarian tumour diagnosis were referred to ILSAR between June 2004 and June 2008 for integrated ultrasonographic evaluation in a Voluson Expert 730 using multifrequency abdominal transductor (1,6-5,3MHz) and multifrequency endocavitary transductor (3,7-9,3 MHz); volumetric study included multiplanar assessment. Malignancy high risk was defined as the presence of 2 or more of the following criteria: more than 10 cm size, presence of vegetations or wall thickness more than 3 mm, solid areas, irregular surface, ascitic fluid, augmented intratumoral vascularization, low-resistance flow at Doppler study. Diagnosis was confirmed by surgery and histopathology. main outcome measures: Integrated ultrasound study predictive value in ovarían tumor benignity and malignity differentiation. Results: From the 101 women with ovarian tumour, 28 cases were classified as high risk for malignancy and 25 of them were malignant at histopathology study; 2D and 3D morphologic criteria analysis showed significant statistical difference between benign and malignant tumors (Anova p=0,001). Resistance index in benign tumors was 0,678 average and in malignant tumors 0,464 (t student p=0,00). Maximum systolic velocity median (MMSV) was 5,367 cm/s in benign tumors and 17,083cm/s in malignant tumors (p<0,001). Integrated US study to detect malignant ovarian tumors sensitivity, specificity and positive predictive values were 92,6%, 95,9% y 89,3% respectively, with 22,5 positive likelihood ratio and 12,9 negative likelihood ratio. Conclusions: Integrated US study of ovarian tumors adequately predicts benign or malignant nature.